Comparison of Solvent Extraction and Static-Headspace Analysis for Determination of Cyanide in Cigarette Smoke by Gas Chromatography Electron Capture Detector - Xie, Yueqin; Yang, Xiaoping; Wang, Liping; Xu, Juan (Asian Journal of Chemistry, 2012)
Two typical pretreatment methods including liquid-liquid extraction and static-headspace analysis had been optimized to determine cyanide in cigarette smoke by gas chromatography equipped with a micro electron capture detector. Within optimization of the extractions, both methods were compared including linearity, limit of detection, repeatability and recovery. Several commercial products were also analyzed and compared. As a conclusion, liquid-liquid extraction possessed higher sensitive while static-headspace analysis was green and broader linearity ranges. Both methods were accuracy and suitable for determine of cyanide in cigarette smoke.